Prospective food diaries demonstrate breastfeeding characteristics in a UK birth cohort. Issue 4 (18th June 2013) - Grimshaw, Kate E.C.; Aksoy, Burcu; Palmer, Anna; Jenner, Katharine; Oliver, Erin M.; Maskell, Joe; Kemp, Terri; Foote, Keith D.; Roberts, Graham C.; Ellahi, Basma; Margetts, Barrie M.
Abstract Breastfeeding duration and exclusive breastfeeding rates are universally below those recommended by World Health Organization. Due to limitations and challenges associated with researching breastfeeding characteristics, the times when exclusivity is likely to be lost and when women are most likely to discontinue breastfeeding have not yet been identified. Prospective food diaries allow reliable description of the dynamics of breastfeeding to be made to help identify these key time periods. Food diaries detailing intake from birth until the cessation of breastfeeding were analysed for 718 infants recruited into a national arm of an international multicentre birth cohort study (EuroPrevall). Analyses included linear regression analysis and Kaplan–Meier time course analysis. Breastfeeding and exclusive breastfeeding cessation rates for younger mothers (<25 years) are high in the first few weeks after delivery but slow markedly in the period 10–12 weeks after delivery. Cessation rates are consistent from 0 to 26 weeks in older mothers. This difference in feeding patterns led to significant differences between the two different age groups at 26 weeks for breastfeeding (P = 0.006) and exclusive breastfeeding at 8 weeks (P = 0.009). Forty‐nine per cent of younger mothers (<25 years) stopped breastfeeding before their infant was 3 weeks old. To increase breastfeeding duration, further work is required to investigate the attitudes and perceptions associated with such high breastfeeding cessation rates in younger mothers during these very early post‐natal weeks.